BEYOND THE VIRUS: HOW COVID-19 ACCELERATED THE SUICIDE CRISIS IN BRAZIL - Andrade, Marcos Vinícius de Oliveira; da Silva, Rubicleis Gomes; Brito, Gabriel Souza de Araujo (Seven Editora, 2026)
The COVID-19 pandemic significantly impacted global mental health, with a noticeable increase in suicide rates. This study analyzes the impact of the pandemic on suicides in Brazil between 2015 and 2023, using a Bayesian time series model to identify the causal relationship between the health crisis and the worsening psychological conditions of the population. The results show a substantial rise in suicide cases starting in 2020, associated with social isolation, economic difficulties, and emotional deprivation. The study highlights the importance of public policies focused on suicide prevention and strengthening social support networks, suggesting that health crises exacerbate mental health issues and require effective responses to minimize their impacts.